The psychosocial impact of caregiving on the family caregivers of chronically ill AIDS and/or HIV patients in home-based care: A qualitative study in Zimbabwe - Claire van Deventer; Anne Wright (AOSIS, 2017)
Background: The family caregiver has a pivotal role to play in the management of the chronically ill HIV and/or AIDS patients. The wellbeing of caregivers is therefore crucial because impairment of their physical or mental health could impact negatively on the management of their HIV-positive family member. The purpose of this qualitative study was to explore the psychosocial impact of caregiving on the family caregiver of the chronically ill HIV and/or AIDS patients in home-based care. Method: Unstructured interviews were conducted with 11 caregivers recruited at an adult HIV clinic at United Bulawayo Hospitals, Bulawayo, Zimbabwe. Relevant demographic information was collected from each participant. The interviews were then transcribed and analysed. Results: Caregivers' biggest challenge was meeting care costs such as food, transport and medical costs. Certain conditions relating to the care-recipient's health and family issues, such as abandonment of the ill patient as well as that of orphans, added to the burden of care. Carers also had to deal with their own health and physical problems. All the above resulted in a spectrum of emotions such as helplessness, sadness, anxiety and anger. Despite this, caregivers also reported on the positive aspects regarding their caregiving role. Conclusion: There were both negative and positive psychosocial experiences by caregivers of HIV and/or AIDS patients. The study highlighted practical areas where support could be provided.